2008
DOI: 10.1007/s00709-007-0275-6
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation and chromosomal rearrangements in reconstructed karyotypes of Hordeum vulgare L.

Abstract: One standard and two reconstructed barley karyotypes were used to study the influence of chromosomal rearrangements on the distribution pattern of DNA methylation detectable at the chromosome level. Data obtained were also compared with Giemsa N-bands and high gene density regions that had been previously described. The effect of chromosomal reconstruction in barley seems to be decidedly prominent in the repositioning of genomic DNA methylation along metaphase chromosomes. In comparison to the standard karyoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…DNMT2, another category of methyltransferase that is conserved in many plants, can methylate tRNA(Asp)C38 in vitro [18]. To date, DNA-MTase have already been identified and characterized in several plant species, including Arabidopsis [19], Oryza sativa [20], Daucus carota [21], Hordeum vulgare [22], Zea mays [23] and Lycopersicon esculentum [24].…”
Section: Introductionmentioning
confidence: 99%
“…DNMT2, another category of methyltransferase that is conserved in many plants, can methylate tRNA(Asp)C38 in vitro [18]. To date, DNA-MTase have already been identified and characterized in several plant species, including Arabidopsis [19], Oryza sativa [20], Daucus carota [21], Hordeum vulgare [22], Zea mays [23] and Lycopersicon esculentum [24].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, few data are available in the literature about the behaviour of homologous chromosomes and possible divergences. Apart from the case of the two X chromosomes in female, in which differences in the methylation pattern between homologous loci in the active versus inactive chromosome have been found (Lyon 1988;Å iroky et al 1998), differences between homologues after anti-5mC binding have been also observed in Allium cepa , Vicia faba (Frediani et al 1996), triticale (Castilho et al 1999), Z. biebersteiniana (Cremonini et al 2003), more recently in barley reconstructed karyotypes (Ruffini Castiglione et al 2008b) and in C. versicolor (Ruffini Castiglione et al 2009). Moreover, differences between homologues have been revealed by asymmetric puffing in polytene chromosomes Cionini et al 1982), by banding techniques (Sumner 1990) and after cytological hybridization with specific DNA sequences both in plants (Durante et al 1977;Loiero et al 1982) and in animals (Hennen et al 1975;London-Vallejo et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of relationships between the t-heterochromatin content and the level of global cytosine methylation in Secale may be also explained by the fact, that not only DNA methylation but also other epigenetic mechanisms are involved in maintaining the constitutive heterochromatin state ( Soppe et al, 2002 ). The evidence comes from the studies on barley, in which differences in chromosomal distribution of constitutive heterochromatin and 5-mC pattern were found ( Castiglione et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%